Organisational Performance Index (The Kenya Institute of Management, 2014)
The OPI Business Excellence Model exists to help organizations improve their performance and succeed in the competitive global marketplace. We are dedicated to improving African organizations regardless of sector, size or structure. The OPI was developed in response to feedback from organization participating in Company of the Year Award (COYA) and SME of the Year Award (SMOYA), who called on the Kenya Institute of Management (KIM) to refine the assessment methodology in order to emphasize the relationship between instilling smart business processes and generating strong business results. Whilst there are numerous management tools and techniques commonly used, the OPI Excellence Model is a practical, non-prescriptive framework which provides a holistic view of the organisation and it can be used to determine how these different methods fit together and complement each other. The Model can therefore be used in conjunction with any number of these tools, based on the needs and function of the organisation, as an overarching framework for developing sustainable excellence. We also administer the Annual Company of the Year Awards (COYA) and the SME of the Year Awards (SMOYA). Our key services are to identify and recognize role-model organizations, share best management practices, and help organizations achieve best-in-class performance levels. The OPI is an excellence model that generates a rating between 1 and 10, which sets a minimum score that an organisation must attain to remain competitive. The attainment of a minimum Organisation Performance Index ( OPI) demonstrates that organisations have applied an organisational strategy that drives effectiveness and competitiveness; failure to attain the minimum OPI demonstrates the organisation has not engaged the processes required to enable world class organisational performance.